2021
DOI: 10.1097/icu.0000000000000768
|View full text |Cite
|
Sign up to set email alerts
|

Alternative therapies for dry eye disease

Abstract: Purpose of reviewDry eye disease (DED) is a multifactorial disease affecting approximately 5-50% of individuals in various populations. Contributors to DED include, but are not limited to, lacrimal gland hypofunction, meibomian gland dysfunction (MGD), ocular surface inflammation, and corneal nerve dysfunction. Current DED treatments target some facets of the disease, such as ocular surface inflammation, but not all individuals experience adequate symptom relief. As such, this review focuses on alternative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 114 publications
1
42
0
Order By: Relevance
“…Generally, nociceptive pain is targeted through use of topical therapies, while neuropathic pain can be treated with oral agents or adjunctive therapies if treatment of nociceptive pain fails and/or a neuropathic component is highly suspected. While many studies have examined treatment outcomes for nociceptive sources of ocular pain ( Dermer et al, 2020 ; Mittal et al, 2021 ), fewer have examined outcomes after treatment of neuropathic ocular pain. Furthermore, available literature typically report on the effects of one therapeutic modality in a limited number of patients ( Ozmen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, nociceptive pain is targeted through use of topical therapies, while neuropathic pain can be treated with oral agents or adjunctive therapies if treatment of nociceptive pain fails and/or a neuropathic component is highly suspected. While many studies have examined treatment outcomes for nociceptive sources of ocular pain ( Dermer et al, 2020 ; Mittal et al, 2021 ), fewer have examined outcomes after treatment of neuropathic ocular pain. Furthermore, available literature typically report on the effects of one therapeutic modality in a limited number of patients ( Ozmen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…27,28 IPL may alleviate MGD and dry eye symptoms for abnormal vascular thrombosis of eye skin, heating meibomian gland with the liquefaction meibomian gland secretion, reducing skin update of epithelial cell, activating fibroblasts and collagen synthesis, eradicating creep mite to reduce bacterial load, adjusting the antiinflammatory agent and matrix metalloproteinases, interfering with the inflammation period, and reducing the level of active oxide. 29,30 In recent years, similar meta-analyses exist concerning IPL therapy in MGD-related dry eye disease. Leng et al 31 found that IPL combined with MGX showed superiority regarding the TBUT (SMD 2.33, 95% CI 1.04;3.61) and OSDI scores (WMD 11.93, 95% CI: 17.10;6.77).…”
Section: Discussionmentioning
confidence: 90%
“…The complications of dryness in DED may vary from a serious abnormal feeling sensation to contact lens intolerance ( 85 ). Currently, the methods of treating DED worldwide mainly include the application of ocular surface lubricants to protect the mucous membrane and the use of anti-ocular surface inflammation drugs, punctual plug placement to reduce tear loss, and physical therapy of the eyelids to restore the meibomian glands ( 86 ). However, various methods can only reduce but not completely eliminate the symptoms of DED.…”
Section: Anti-inflammatory Treatment For Dry Eye Diseasementioning
confidence: 99%